An Improved Momentum-exchanged Immersed Boundary-based Lattice Boltzmann Method for Incompressible Viscous Thermal Flows. (2015) - Chen, Mu-Feng; Niu, Xiao-Dong; Ma, Yi-Ren; Yamaguchi, H.; Iwamoto, Y.
Abstract: An improved momentum-exchanged immersed boundary-based lattice Boltzmann method (MEIB-LBM) is proposed for incompressible viscous flows in this paper. In present work, we come back to the intrinsic feature of LBM, which uses the density distribution function as a dependent variable to evolve the flow field, and use the non-equilibrium density distribution function correction at the neighbour Euler mesh points to satisfy the non-slip boundary condition on the immersed boundary. The improvements for the original MEIB-LBM are that the intrinsic feature of LBM is kept and the flow penetration is removed. Examples, including force convection over a stationary heated circular cylinder for heat flux condition, and natural convection with a buoyant circle particle in viscous fluid, are provided to validate the present method.